(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
Audiovisual translation (AVT) is a multidisciplinary field that encompasses linguistic, cultural, and technical aspects of translating audiovisual content such as films, television programs, online videos, and educational materials. This chapter provides a scientific review of the theoretical development, classification, and methodological foundations of AVT, focusing on the role of linguistic and cultural features in the translation process. The discussion contextualizes AVT within modern translation studies approaches, including functionalist theory, equivalence theories, and relevance theory, highlighting their applicability to audiovisual translation practice. The study also examines how linguopragmatic and stylistic approaches influence translation strategies, and emphasizes the importance of cultural coherence and effective communication in ensuring fidelity, intelligibility, and audience engagement. The purpose of this research is to identify the main forms of AVT, explore the interplay of linguistic and cultural features, and demonstrate how these factors affect communicative effectiveness in translation.